Immunosuppressive drugs and fertility. Issue 1 (December 2015) - Leroy, Clara; Rigot, Jean-Marc; Leroy, Maryse; Decanter, Christine; Le Mapihan, Kristell; Parent, Anne-Sophie; Le Guillou, Anne-Claire; Yakoub-Agha, Ibrahim; Dharancy, Sébastien; Noel, Christian; Vantyghem, Marie-Christine
Abstract Immunosuppressive drugs are used in the treatment of inflammatory and autoimmune diseases, as well as in transplantation. Frequently prescribed in young people, these treatments may have deleterious effects on fertility, pregnancy outcomes and the unborn child. This review aims to summarize the main gonadal side effects of immunosuppressants, to detail the effects on fertility and pregnancy of each class of drug, and to provide recommendations on the management of patients who are seen prior to starting or who are already receiving immunosuppressive treatment, allowing them in due course to bear children. The recommendations for use are established with a rather low level of proof, which needs to be taken into account in the patient management. Methotrexate, mycophenolate, and le- and teri-flunomide, cyclophosphamide, mitoxanthrone are contraindicated if pregnancy is desired due to their teratogenic effects, as well as gonadotoxic effects in the case of cyclophosphamide. Anti-TNF-alpha and mTOR-inhibitors are to be used cautiously if pregnancy is desired, since experience using these drugs is still relatively scarce. Azathioprine, glucocorticoids, mesalazine, anticalcineurins such as cyclosporine and tacrolimus, ß-interferon, glatiramer-acetate and chloroquine can be used during pregnancy, bearing in mind however that side effects may still occur. Experience is limited concerning natalizumab, fingolimod, dimethyl-fumarate and induction treatments. Conclusion: At the time of prescription, patients must be informed of the possible consequences of immunosuppressants on fertility and of the need for contraception. Pregnancy must be planned and the treatment modified if necessary in a pre-conception time period adapted to the half-life of the drug, imperatively in relation with the prescriber of the immunosuppressive drugs.